VALUES DEVELOPMENT THROUGH GYMNASTIC EDUCATION IN PRESCHOOL CHILDREN - Sinem YÜRÜK; Sibel SÖNMEZ; Feride Zişan KAZAK (University of Ljubljana Press (Založba Univerze v Ljubljani), 2024)
Physical education and sports are at the forefront of many schools of thought when it comes to values education since sport has the power to provide a universal framework for learning values. For this reason, the aim of this study is to examine the development of values in children aged four and five who start their gymnastics education in early childhood. In the experimentally planned study, the children's families filled the values scale as a pre-test and post-test, and the changes were examined. The population of the research group consisted of children aged four to five who attended the gymnastics course opened by a private club in the Akhisar district of Manisa during the summer period. The sample group consisted of 49 children whose consent was obtained after informing their families. The Preschool Values Scale Family Form (PVSFF), developed by Neslitürk and Çeliköz (2015), was used as a measurement tool. Although there was no significant difference between the pre-test and post-test mean scores of the Preschool Values Scale Family Form, a significant difference was found only in the responsibility sub-dimension of the scale. Therefore, it is understood that children can gain values, especially responsibility, through lifelong game-based sports. Considering that learning through game is important in early childhood, it is thought that emphasizing the concept of values in the movement or sports education programs to be structured and to inform the teachers, coaches or consultants working in this field is crucial.